Odpowiedzi

2010-03-19T15:39:18+01:00
A) 4x -6 +12= x-3x -6
4x + 6 = 2x -6/ -24
2x +6 = -6 / -6
2x= -12
x= -6
b)6-4x+1=3x-3
7-4x=3x-3 / -7
-4x=3x -10 / -3x
-7x= -10
x= 0,7
c) 24y-16-7y= 60-15y+13y
17y-16=60-2y
19y=76/; 19
y=4
d)5x+2-3x+0,6 6,4x-9,6
2 3 2
2010-03-19T15:41:51+01:00
A) 2(2x-3)+12=x-3(x+2)
4x-6+12=x-3x-6
4x-x+3x=-6+6-12
6x=-12/:6
x=-2
b)2(3-2x)+1=3(x-1)
6-4x+1=3x-3
-4x-3x=-3-6-1
-7x=-10/;(-7)
x=¹⁰/₇=1 ³/₇
c)8(3y-2)-7y=5(12-3y)+13y
24y-16-7y=60-15y+13y
24y-7y+15y-13y=60+16
19y=76/:19
y=4
d)2(2,5x-1)-3(x-0,2)=3,2(2x-3)
5x-2-3x+0,6=6,4x-9,6
5x-3x-6,4x=-9,6+2-0,6
-4,4x=-8,2/:(-4,4)
x=1,863(63636363636)
2 3 2